Improving implementation : organisational change and project management - Wanna, John (ANZSOG (Series), 2007)
"The business of government is necessarily diverse, changing and of considerable scale. A focus on improving the implementation of government programs and initiatives is important because the community expects the Government to deliver on its policies, as does the Government. The papers included in this collection address numerous aspects of improving implementation. They were initially presented at the Project Management and Organisational Change conference held in Canberra in February 2006, the first annual research conference organised by ANZSOG in conjunction with the Department of the Prime Minister and Cabinet. This collection represents a comprehensive drawing together of experience and insight from both practitioners and academic researchers, with speakers including top public sector executives from the Australian jurisdictions as well as representatives from the United Kingdom, Canada and New Zealand."--ANU Press.